Financial access, governance and insurance sector development in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
Purpose - This study investigates the role of financial access in moderating the effect of governance on insurance consumption in 42 Sub-Saharan African countries using data for the period 2004-2014. Design/methodology/approach - Two life insurance indicators are used, notably: life insurance and non-life insurance. Six governance measurements are also used, namely: political stability, "voice & accountability", government effectiveness, regulation quality, corruption-control and the rule of law. The empirical evidence is based on the Generalised Method of Moments (GMM) and Least Squares Dummy Variable Corrected (LSDVC) estimators. Findings - Estimations from the LSDVC are not significant while the following main findings are established from the GMM. First, financial access promotes life insurance through channels of political stability, "voice & accountability", government effectiveness, the rule of law and corruption-control. Second, financial access also stimulates non-life insurance via governance mechanisms of political stability, "voice & accountability", government effectiveness, regulation quality, the rule of law and corruption-control. Originality/value - This research complements the sparse literature on insurance promotion in Africa by engaging the hitherto unexplored role of financial access through governance channels.
Keywords: I28; I30; G20; O16; O55; 330; Insurance; Finance; Governance; Sub-Saharan Africa